PERSEPSI PENGUNJUNG DALAM PENGEMBANGAN WISATA ALAM BUKIT KANDIS KABUPATEN BENGKULU TENGAH - Yurike, Yurike; Wiryono, Wiryono; Lestari, Aisah (MAKILA, 2024)
Visitor perceptions are very important in developing natural tourism on post-mining land. Post-mining land often offers the potential to be developed into a unique tourist destination with its own characteristics. One of the post-mining natural tourist attractions that is very interesting for visitors in Central Bengkulu Regency is the Kandis Hill natural tourist attraction. This research aims to determine visitor perceptions in the development of Kandis Hill natural tourism, Central Bengkulu Regency. The research uses qualitative descriptive methods. Research variables include beauty, cleanliness, security, spatial planning, staff reception, public facilities, signal conditions, road access, transportation, accommodation, security. Primary data was obtained through observation and interviews using a questionnaire, then analyzed using a Likert scale. The results of the research were that the highest visitor perception regarding beauty reached 94% with an adequate category and the lowest regarding cleanliness and staff reception with a score of 20% in the inadequate category. Another thing that needs attention is public facilities that are damaged and not functioning. Currently, the management of Kandis Hill is still in the hands of the regional government. For this reason, the government needs to empower the community around the Kandis Hill area to manage the area so that it is better managed and can develop the economy of the community around the area